Socioeconomic differences in discharge against medical advice and hospital admission among emergency department visits associated with substance use in the United States - Mojtahedi, Zahra; Kim, Pearl; Yoo, Ji; Wang, Binglong; Shen, Jay J. (Frontiers in Public Health, 2025)
BackgroundDischarge against medical advice (DAMA) and inpatient admission (IA) among emergency department (ED) visits are two important outcomes in hospital utilization, while the first one has been mainly considered a negative outcome.AimsThis study aimed to examine the association of socioeconomic factors with DAMA and IA among ED visits with substance use (age 12–64 years) before and after the COVID-19 pandemic.MethodsThe study retrospectively analyzed the Nationwide Emergency Department Sample (NEDS) from 2019 to 2020. The International Classification of Diseases 10th Revision (ICD-10) codes were used to identify opioid, cannabis, and alcohol use, and smoking.ResultsThe pandemic was significantly associated with higher odds of IA (OR 1.04, CI 1.02–1.06). Female gender and rural hospitals were adversely associated with both DAMA and IA, but lower household incomes were positively and negatively associated with DAMA and IA, respectively. Race and health insurance were partly differently associated with these outcomes. Asian patients exhibited significantly lower odds (OR 0.82, CI 0.71–0.88) regarding DAMA. Black (OR 0.79, CI 0.78–0.80) and Native American patients (OR 0.87, CI 0.82–0.90) exhibited lower odds, and Hispanic (OR 1.05, CI 1.03–1.06) and Asian patients (OR 1.40, CI 1.33–1.44) had higher odds compared to White patients in terms of AI. Except for self-pay, which was associated with lower odds of IA, Medicaid, self-pay, and free care were significantly associated with higher odds of DAMA and IA. Our results also showed that the COVID-19 pandemic affected the association of health insurance with IA, but not with DAMA.ConclusionThese findings highlight the complex association of socioeconomic factors with DAMA and IA. By addressing these differences within the hospital setting, providers can mitigate the negative consequences of substance use on patient health and reduce the burden on healthcare systems.